Microsurgery for intracranial aneurysms: A qualitative survey on technical challenges and technological solutions - Muirhead, W. R.; Layard Horsfall, H.; Khan, D. Z.; Koh, C.; Grover, P. J.; Toma, A. K.; Castanho, P.; Stoyanov, D.; Marcus, H. J.; Murphy, M. (Frontiers in Surgery, 2022)
Introduction: Microsurgery for the clipping of intracranial aneurysms remains a technically challenging and high-risk area of neurosurgery. We aimed to describe the technical challenges of aneurysm surgery, and the scope for technological innovations to overcome these barriers from the perspective of practising neurovascular surgeons. Materials and Methods: Consultant neurovascular surgeons and members of the British Neurovascular Group (BNVG) were electronically invited to participate in an online survey regarding surgery for both ruptured and unruptured aneurysms. The free text survey asked three questions: what they consider to be the principle technical barriers to aneurysm clipping; what technological advances have previously contributed to improving the safety and efficacy of aneurysm clipping; and finally, what technological advances do they anticipate improving the safety and efficacy of aneurysm clipping in the future. Qualitative synthesis of responses was performed using multi-rater emergent thematic analysis. Results: The most significant reported historical advances in aneurysm surgery fell into five themes: 1) Optimising Clip Placement 2) Minimising Brain Retraction 3) Tissue Handling 4) Visualisation and Orientation 5) Management of Intraoperative Rupture. The overwhelmingly most reported innovation was Indocyanine Green Angiography (84% of respondents). The three most commonly cited future advances were Hybrid Surgical and Endovascular Techniques, Advances in Intraoperative Imaging and Patient Specific Simulation and Planning. Conclusions: While some surgeons perceive that the rate of innovation in aneurysm clipping has been dwarfed in recent years by endovascular techniques, surgeons surveyed highlighted a broad range of future technologies which have potential to continue to improve the safety of aneurysm surgery in future.